Groundwater Vulnerability Comparison Using DRASTIC and GOD Methods in Surakarta City - Koesuma, Sorja; Ramelan, Ari Handono; Sutarno, Doddy (Faculty of Geography, Universitas Gadjah Mada, 2024)
Demographic growth, urbanization, economic development, agriculture, and consumption per capita have increased the demand for water resources. The population density of Surakarta affects the city’s ability to fulfil its residents’ clean water requirements. As an urban region, Surakarta may be impacted by development activities that degrade the quality and quantity of groundwater. This growing demand should be balanced against effective management of water source regions. This research aims to investigate groundwater vulnerability in Surakarta City. We employed the DRASTIC and GOD methods and compared both results. These methods used the overlay and indexing approaches using GIS based on field data and secondary data such as drill, rainfall, and topographic data. The results of DRASTIC show three types of vulnerability: high (0.21%; 9.87 ha), moderate (94.22%; 4,355.98 ha), and low (5.56%; 257.25 ha), while GOD method results in high (7.03%; 324.96 ha), moderate (52.90%; 2,445.84 ha), low (38.69%; 1,788.81 ha), and negligible (1.37%; 63.49 ha). Based on both methods, we identified Banjarsari district as a location with high groundwater vulnerability. The correlation coefficient between the two methods is 0.511. This value shows that the correlation criteria are acceptable and comparable. This research can be used by local authorities and policymakers to manage groundwater resources.